Agri-Food Waste from Apple, Pear, and Sugar Beet as a Source of Protective Bioactive Molecules for Endothelial Dysfunction and Its Major Complications - Cristiana Caliceti; Marco Malaguti; Luisa Marracino; Maria Cristina Barbalace; Paola Rizzo; Silvana Hrelia (MDPI AG, 2022)
Endothelial damage is recognized as the initial step that precedes several cardiovascular diseases (CVD), such as atherosclerosis, hypertension, and coronary artery disease. It has been demonstrated that the best treatment for CVD is prevention, and, in the frame of a healthy lifestyle, the consumption of vegetables, rich in bioactive molecules, appears effective at reducing the risk of CVD. In this context, the large amount of agri-food industry waste, considered a global problem due to its environmental and economic impact, represents an unexplored source of bioactive compounds. This review provides a summary regarding the possible exploitation of waste or by-products derived by the processing of three traditional Italian crops-apple, pear, and sugar beet-as a source of bioactive molecules to protect endothelial function. Particular attention has been given to the bioactive chemical profile of these pomaces and their efficacy in various pathological conditions related to endothelial dysfunction. The waste matrices of apple, pear, and sugar beet crops can represent promising starting material for producing "upcycled" products with functional applications, such as the prevention of endothelial dysfunction linked to cardiovascular diseases.